EVALUASI KETEPATAN PEMILIHAN MEDIA PEMBELAJARAN JARAK JAUH DI MASA PANDEMI COVID-19 - Agus Salim; Hamsi Mansur; Agus Hadi Utama (Al-Falah: Jurnal Ilmiah Keislaman dan Kemasyarakatan, 2020)
Distance learning media is a learning component that is an integral part of the learning process during the Covid-19 pandemic. The use of distance learning media can help the process of delivering messages from teachers to students to be more effective. Selection of the right distance learning media requires the use of certain principles and criteria so that it is appropriate in choosing a distance learning media because each learning media should have different characteristics and usability specifications. This study aims to conduct a summative evaluation of the accuracy of selecting distance learning media during the Covid-19 pandemic. Distance learning media that will be summative evaluation are all subjects found by researchers in junior high schools throughout Banjarmasin City through the population method and the sample using purposive random sampling technique as many as 5 Banjarmasin City Junior High Schools. The data analysis technique in this summative evaluation is carried out in a descriptive-qualitative manner using a model of the principles and criteria used to evaluate the accuracy of the selection of distance learning media which consists of four components, namely: suitability with the material, suitability with student characteristics, suitability with learning styles. students, and the suitability of supporting facilities. The results showed that the mapping of the accuracy of the selection of distance learning media in the Banjarmasin City Junior High School has fulfilled the four criteria for the accuracy of selecting the right learning media with good categories. Keywords: Evaluation, Accuracy of Distance Learning Media Selection